Testing as one of the innovative methods of organizing training and control at the lesson of the Russian language and literature (Journal of Pedagogical Inventions and Practices, 2022)
In the modern learning process, non-traditional (innovative) for domestic education methods, forms, means of training and control have become widespread. These include tests. The system of test tasks, have a specific organization and are created in order to identify the special abilities of students; measuring the level of knowledge; evaluation of the results achieved by them in the learning process. The test as a form of control allows all students to work simultaneously in the same conditions and record the performance with symbols.